Strained BaTiO3 thin films via in-situ crystallization using atomic layer deposition on SrTiO3 substrate - Choi, Heung Yoon; Jeon, Jae Deock; Kim, Se Eun; Jang, Seo Young; Sung, Ju Young; Lee, Sang Woon (Materials Science in Semiconductor Processing, 2023)
The interface engineering of oxide heterostructures, such as BaTiO3 (BTO)/SrTiO3 (STO), has received considerable attention because of their interesting physical/electrical properties. In this study, the in-situ crystallization of BTO thin film was achieved using a high temperature (∼350 °C) atomic layer deposition (ALD) process, which enabled the formation of strained BTO thin films on the STO substrate. A compressive strain was introduced along the in-plane direction of the BTO film, resulting in a 1.5% decrease in the lattice constant of BTO film while an in-plane tensile strain was induced in the STO layer (0.8% increase in the lattice constant). The in-situ crystallization of BTO thin films grown by ALD allowed the formation of a strained interface at the BTO/STO heterostructure.
Keywords: Atomic-layer deposition; BaTiO 3; Compressive strain; Deposition process; Highest temperature; In-situ crystallization; Interface engineering; Oxide heterostructures; SrTiO 3; Thin-films; Atomic layer deposition; BaTiO3; In-situ crystallization; Interface engineering; SrTiO3; Strain